The heritage of Hohhot: a journey through a community Masjid in China - Soomro, Ali Raza; Azmin, Aida Kesuma (Kulliyyah of Architecture, International Islamic University Malaysia, 2016)
Heritage study is a sign of not only the potentials of creating symbols in a city, but also is a testament to the potentialities of adaptive reuse of valuable old structures. The Great Masjid of Hohot, also known as the Qingchen Dasi, symbolises not only the capacities of the heritage structures to be adapted but also symbolises significances of Muslims as a growing minority in a predominantly non-Muslim country. This chapter explores the history, functions, planning and architecture of Great Masjid of Hohot as an outcome of heritage study conducted by department of architecture of Kulliyyah of architecture & environmental design of International Islamic University of Malaysia.